Technology based industrial product-services supporting robustness in manufacturing systems. Issue 12 (2016) - Colledani, M.; Silipo, L.; Yemane, A.; Lanza, G.; Strieker, N.; Ziprani, F.; Fogliazza, G.
Abstract: Uncertainty affecting manufacturing systems or networks asks for approaches able to smoothing the negative effects of disturbances coming both from the plant and supply chain levels. Thus, the objective of this paper is to investigate the capability of product-services business models of increasing companies robustness, towards internal and external disturbances in highly dynamic environments. This work is part of the EU project RobustPlaNet, which investigates this topic in the context of three industrial areas, i.e. automotive, aerospace and industrial automation. The analysis is carried out on a case study in the field of equipment reliability in order to demonstrate the formalization of business models for industrial product-services that support systems' robustness.